2010
DOI: 10.1109/tvlsi.2008.2008810
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of NBTI Effect on Combinational Circuit: Modeling, Simulation, and Analysis

Abstract: Positive acceleration in the head to toe direction (+Gz) causes a reduction in blood circulation to the head which adversely affects the central nervous system and causes a decrease in vision. It has been established that Positive Pressure Breathing enhances +Gz tolerance by increasing head level blood prerssure.Utilizing the NAWC centrifuge, eight subjects outfitted with Navy Combat Edge (NCE) protective systems were exposed to a series of +Gz Rapid onset Rate (ROR) profiles and Positive Pressure Breathing sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
137
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(141 citation statements)
references
References 21 publications
4
137
0
Order By: Relevance
“…Thus, it becomes impractical to perform simulation in order to predict ∆V th . However, various recent studies have shown that it is possible to obtain a closed form for the upper bound on the ∆V th as a function of the duty cycle α, T clk and t [15]. In fact, the models of PBTI and NBTI are similar to each other.…”
Section: Modeling Bti-induced Cmos Device Agingmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, it becomes impractical to perform simulation in order to predict ∆V th . However, various recent studies have shown that it is possible to obtain a closed form for the upper bound on the ∆V th as a function of the duty cycle α, T clk and t [15]. In fact, the models of PBTI and NBTI are similar to each other.…”
Section: Modeling Bti-induced Cmos Device Agingmentioning
confidence: 99%
“…In fact, the models of PBTI and NBTI are similar to each other. The BTI effect on V th can be calculated as follows [15],…”
Section: Modeling Bti-induced Cmos Device Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…This Vth drift strongly depends on the amount of time during which a PMOS transistor is stressed. On the other hand, when the stress condition is relaxed, the aging can be recovered partially, and the Vth decreases toward the nominal value [5], [6]. In SRAMs, the value dependence of NBTI is weaker than in logic circuits: given the symmetric structure of a 6T-SRAM cell, one PMOS is always under stress as long as it stores any value so the SRAM cell structure degrades continually [39], [23].…”
Section: Introductionmentioning
confidence: 99%